치주수술 후 치아상실에 대한 환자관련, 치아관련 위험요소 - 후향적 연구 - 송종근(Jong-Geun Song); 이성조(Sung-Jo Lee); 휴팜동(Pham-Duong Hieu); 신현승(Hyun-Seung Shin); 조인우(In-Woo Cho) (Journal of dental rehabilitation and applied science, 2023)
Purpose: The purpose of this study is to analyze the prognostic factors related to tooth loss after 5 years of periodontal surgery in periodontal disease patients. Materials and Methods: From January to December 2017, 22 patients and 124 teeth who underwent periodontal treatment through periodontal surgery were targeted. At the time of treatment, the measured values were evaluated after recording the maximum probing depth, average periodontal probing depth, number of root, furcation involvement, pulp vitality, and prosthesis state on the day of periodontal surgery. Based on the initial records at the time of visit, patient-related factors were gender, age, smoking, tooth loss due to periodontal disease at the time of first visit, diabetes, and maintenance period. The influence of each factor on tooth loss was evaluated. Results: As a result of examining the influence of tooth-related factors on tooth loss, the maximum probing depth depth (P: 0.000), bone loss (P: 0.021) was found to have a significant effect on tooth loss. Conclusion: As a result of examining the influence of patient-related factors on tooth loss, any variables had no significant effect. Bone loss, maximum probing depth acted as statistically significant prognostic factors for tooth loss in patients who underwent periodontal surgery. 목적: 이 연구의 목적은 치주질환자를 대상으로 치주판막술 시행 5년 후 치아의 상실여부를 파악한 뒤 치아 상실과 관련된 예후 요인을 분석하는 것이다. 연구 재료 및 방법: 2017년 1월부터 12월까지 치주치료를 시행한 22명의 환자, 124개의 치아를 대상으로 하였다. 치아 관련요인은 치료 당시에 수술을 진행한 술자에 의해 임상적으로 기록된 요인으로 치주수술 당일 최대 치주낭 깊이, 치근의 수, 치근 이개부 이환, 근관치료 여부, 보철상태를 기록하였다. 내원 당시의 초진 기록을 기준으로 환자관련 요인은 성별, 나이, 흡연 여부, 첫 내원 당시 치주질환으로 상실된 치아 여부, 당뇨병 이환 여부, 5년간 유지관리 응답도가 있으며 각각 요인들을 기록하였다. 각각의 요인들의 치아 상실 여부와 관련한 영향력을 평가하였다. 결과: 치아 관련요인이 발치에 미치는 영향력을 살펴본 결과 최대 치주낭 깊이, 골 소실, 치근 이개부 이환 중 치주낭 깊이(P : 0.000), 골 소실(P : 0.021)이 발치에 유의미한 영향을 미치는 것으로 나타났다. 특히, 최대 치주낭 깊이의 영향력이 가장 높은 것으로 나타났다. 환자 관련 요인은 치아발치에 유의한 결과를 보이지 않았다. 결론: 치주판막술을 시행한 환자에서 골 소실, 최대 치주낭 깊이가 치아 상실과 관련하여 통계적으로 유의성 있는 예후 요인으로 작용하였다.